The Existence of Hizbut Tahrir Indonesia's Da'wah after Dissolution - Sabiruddin, Sabiruddin; Taqiyuddin, Muhammad Fikri; Ridwan, Muhammad; Sarwan, Sarwan; Mardiana, Puja Dikusuma (International Journal of Islamic Studies Higher Education, 2023)
Hizbut Tahrir Indonesia is a political da'wah organization that focuses on spreading Islamic ideology through scientific and intellectual approaches. This research aims to analyze the da'wah strategy, political ideas, and reasons for the dissolution of Hizbut Tahrir Indonesia in the context of the spread of ideology through intellectual-based channels. Tsaqofah and evaluation of the strategic ideas proposed to realize their ideals. This research uses a qualitative method with a literature study approach, which is analyzed through three stages: data reduction, data presentation, and conclusion. The research results show that Hizbut Tahrir Indonesia prefers a da'wah-based path tsaqofah (scientific) as its main basis, which is realized through seminars, discussions, and conferences to spread its ideas. With this approach, Hizbut Tahrir Indonesia is known as an intellectual movement that does not involve physical action like other radical organizations. Hizbut Tahrir Indonesia also carries out two phases of organized struggle, namely (i) Tafa'ul ma'al umma, the phase of socializing ideas to the general public, and (ii) Tafa'ul bil aam, the phase of interaction of ideas in public space. Apart from that, Hizbut Tahrir Indonesia proposed two strategic ideas to realize its ideals, namely (i) adopting the principle of moderation in Nahdlatul Ulama's preaching which various groups accept, and (ii) taking a step back to move forward by joining a political party as a first step to achieve long-term goals. This research provides insight into the da'wah strategy and dynamics of the Indonesian Hizbut Tahrir political movement, as well as its relevance in Indonesia's social and political context.